Spatiotemporal Characteristics of the Domestic Water Consumption Patterns and Related Issues in Sri Lanka - Kaushalya, G.N.; Wijeratne, V.P.I.S.; Manawadu, L. (International Journal of Scientific and Research Publications, 2020)
Water is essential for all sorts of growth and development of humankind, animal, and plant. One of the most important uses of water is for domestic purpose and it is the third-largest water consumer from total water consumption in the world. This study mainly explored the spatiotemporal patterns of domestic water consumption and related issues in semi-urban and rural areas. Primary data collection mainly conducted with a hundred (N=100) sample household questionnaires and sample households were selected based on main drinking water sources (groundwater and tap water) using a stratified random sampling method. Correlation, Kernel density, nearest neighbor analysis, and interpolation techniques were used to fulfill the main research objective of the study. All analyses carried out using ArcGIS 10.1 and Excel 2013 software. The study found 392 randomly distributed domestic groundwater wells for daily activities. In the wet season, most households (65%) using the groundwater for their daily purposes but in the dry season, most of them (51%) use the government water supply. The daily average water consumption of the study area is 119.44L per person per capita per day. Bathing, toilet, cloth washing, and cooking and washing dishes were identified as the higher water consumption activities around the study area. The amounts of water consumption by each activity were 31.54%, 24.2%, 23.66%, and 10.33% respectively. However, water consumption patterns can be changed due to income, the number of household members, age, and distance. Also, the Uneven distribution of drinking water sources, spatial and time-related issues, insufficient water storage facilities, water scarcity, poor water management were identified as major issues related to domestic water consumption in the study area. Finally, it is hoped that the results of the study would benefit the policy and planning executives in the study area in optimizing the existing water resources for sustainable development.
Keywords: Domestic Water Consumption, Spatiotemporal variability, ArcGIS 10.1, Water Supply